Neigbourhood Factors on Mental Health Questionnaire: Development, Validity, and Reliability among Malaysian Adolescents - Zahir Izuan Azhar,; Shamsul Azhar Shah,; Susan, MK Tan; Syed Sharizman Syed Abdul Rahim, (Universiti Kebangsaan Malaysia, 2016)
Introduction: The risk factors associated with mental health among adolescents are usually described by researchers at an individual level. Neighbourhood factors and health have opened a new insight into the field of epidemiology. The aim of this study was to assess the reliability and validity of a newly developed Neighbourhood Factors on Mental Health Questionnaire among Malaysian adolescents.